1978
DOI: 10.1093/jn/108.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Triglycerides on Blood and Tissue Cholesterol of Calves

Abstract: Blood and tissue cholesterol responses were measured in six groups of four calves each fed for 24 weeks reconstituted nonfat dry fat milk in which 30% of calories was derived from one of the following: soybean oil (SBO), beef tallow (T), medium-chain triglycerides (MCT), and 1:1 soybean-oil tallow (SBO/T) combination. Two groups of four calves each also were fed SBO-milk plus dry feed and T-milk plus dry feed, respectively. Blood cholesterol concentration was significantly greater in SBO-fed calves than in T-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…It is possible that the reduced cholesterol and TAG concentrations in serum by SL diet are due to 8:0, n-3 PUFA, or both. However, the effects of MCFA on cholesterol and TAG concentrations in blood are not clear (Kaunitz et al 1958;Stewart et al 1978;Swift et al 1992;Cater el al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the reduced cholesterol and TAG concentrations in serum by SL diet are due to 8:0, n-3 PUFA, or both. However, the effects of MCFA on cholesterol and TAG concentrations in blood are not clear (Kaunitz et al 1958;Stewart et al 1978;Swift et al 1992;Cater el al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…MCTs have also been reported to act as antioxidants and reduce tissue requirements for vitamin E 6 . The anti-coagulation effect of MCTs helps to prevent artherosclerosis 7 . The experiment of Kaunitz et al with rabbit indicated that MCTs could have a positive effect on autoimmune reactions characteristic of the ageing process 8 .…”
mentioning
confidence: 99%
“…The ease of hydrolysis and absorption of medium-chain triacylglycerols (MCT) makes them useful as a dense source of energy in patients with pancreatic insufficiency and fat malabsorption problems. MCT also lowers both serum choles-terol and tissue cholesterol in animals and man, and even more significantly so than conventional polyunsaturated oils (3). Because of their reduced caloric value (8.3 kcal for MCT and 9 kcal for LCT) and lower tendency to deposit as depot fat (4), SL from medium-or short-chain fatty acids and longchain fatty acids (LCFA) can be used to produce reducedcalorie foods.…”
mentioning
confidence: 99%